The impact of implementing quality in the forensic morgue in Mecca - Nawaf.N.Ahmed; Hani.M.Alqurashi; Ayman.H.Ahmad; Hani.MS.Sharkhan; Ameen.H.Alansari; Mohammed.A.Boties; Yasser.K.Alghamdi; Abdullah.M.Alahmadi; Dhakeelallah.D.Almusoudi; Salem A.Alghamdi; Abdulhadi .A . Alqurashi; Hisham. N. Awlia (International Journal of Medical Toxicology and Legal Medicine, 2024)
This current study aims to know the impact of applying quality standards in the forensic medicine refrigerator, and the impact of employees applying quality standards at work. The questionnaire was prepared via Google Drive and distributed to all employees of the Forensic Medical Services Center in Mecca (administrators, technicians, and doctors). The questionnaire was distributed to them via the social networking program (WhatsApp), and responses were obtained via email. It concluded that the principles and basics of quality are applied in the forensic morgue at a rate of 81.8%, which is a good percentage.